The Gospel and Money: A Neo-Pentecostal Re-reading of Luke-Acts 67 - Mokhoathi, Joel (Commercialisation of Religion in South Africa: A Pentecostal Approach, 2023)
There has been an increase in the number of money-driven religions in which the commercialisation of religion is a reasonable if not indispensable component of belief. The Christian religion is not the exception, but thrives and continues to sustain its operations through the aid of money. In fact, the Judeo-Christian traditions trace the production and ownership of money to God, who declared that ‘silver and gold’ belongs to him, thereby defining it as a common good from which all Christians can benefit. However, how this should practice should be performed is not clear, as the Lukan materials do not provide any general guidelines. As a result, there are three theories that inform the ownership and use of money within the Christian context. These are, namely: (1) the dispossession of goods, (2) the common possession, and (3) almsgiving. Using a qualitative research approach in the form of document analysis, this paper aims to look at the dependence of religion (Christianity in particular) on money; to review the three major theories that inform the ownership and use of money from the Lukan materials, with a specific focus on Luke-Acts; and to use the three theories as a backdrop in reflecting on the practice of ownership and use of money in neo-Pentecostal Churches within the South African context.
free